Open access to CGIAR research – next steps with our CGSpace community - Ballantyne, Peter G. (International Livestock Research Institute, 2023)
For open access week in 2022, we celebrated a major milestone: 100,000 knowledge products published through our joint CGSpace repository of research outputs. In the past 12 months, CGSpace has become well–established and is now our collaborative platform to publish, make available and disseminate the collective work of hundreds of scientists working together on 35+ agrifood research initiatives and platforms. Alongside these efforts, in 2023, working as a community of practitioners, the team behind CGSpace is putting the next version of CGSpace in place.